Evaluation of two different orally disintegrating tablet formulations containing flurbiprofen inclusion complex and its solid dispersion - Ozyilmaz, Emine Dilek; Comoglu, Tansel (Pharmacotherapy Group, 2023)
Purpose: To prepare orally dispersible tablet formulations (ODTs) by increasing the solubility of flurbiprofen (FB), which has low water solubility. Methods: The ODTs were prepared using direct compression method the inclusion complexes and solid dispersions with the highest solubility were further evaluated. Flurbiprofen, polyvinylpyrrolidone (PVP) solid dispersions were blended together by solvent evaporation method, while the inclusion complexes were co-formulated with beta cyclodextrin (beta-CD) by kneading at three different ratios. The ODTs were characterized by differential scanning calorimetry (DSC), Fourier transform infra-red spectroscopy (FTIR) and for their micromeritic properties. In addition, the solubility properties of the inclusion complexes and solid dispersions in distilled water were compared with the solubility of flurbiprofen. Results: The highest solubility value of PVP-FB solid dispersions was found at 1:6 (0.501 mg/mL) and for FB beta-CD inclusion complex at 1:2 (0.701 mg/mL). Angle of repose ranged from 28.09 - 32.15 (o); Carr's index from 7.59 to 10.01; and Hausner's ration from 1.05 - 1.15. DSC and spectral studies indicate that FB did not chemically interact with either PVP or beta-CD. Conclusion: Orally dispersible tablets containing flurbiprofen beta-CD complex exhibit significantly higher bioavailability than the drug alone due to its increased solubility.
Keywords: Flurbiprofen; Solubility; Orally disintegration tablets; Inclusion complex; Solid dispersion